Gram-scale production of forskolin in yeast through biosynthetic network elucidation and pathway optimization - Meiling Jiang; Hao Tang; Ying Ma; Zhenjiang Tian; Wenbo Xu; Xinqi Song; Lan Kang; Luqi Huang; Yating Hu (Bioresource Technology, 2026)

Dominant taxa, rather than Shannon diversity, drive zooplankton stability across scales - Zeng Lei; Zhang Rui; Chen Yuxiang; Liu Beibei; Zheng Tingting; Li Wuhui; Tang Yuqi; Li Yating; Xiang Yuqi; Nie Mengwei; Chen Guobao (Estuarine, Coastal and Shelf Science, 2026)

Advances in MOF-enabled food preservation and packaging: A critical review of structure-function relationships, functionalization strategies, applications, and safety - Yinghua Tang; Yuqin Feng; Xuefeng Liu; Kuiran Liu; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Research International, 2026)

Electrospun nanofiber interfaces for aquatic products preservation: spoilage microenvironments, molecular interactions, and mechanism-oriented design strategies - Kuiran Liu; Yuqin Feng; Xuefeng Liu; Yinghua Tang; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Bioscience, 2026)

Generation and application of monoclonal antibodies against CD4-1 and CD8α for characterizing T cell subsets in grass carp (Ctenopharyngodon idella) - Haokai Chen; Ming Geng; Kang Li; Zhichao Fang; Yating Zhu; Yuqing Yang; Shiqi Tang; Jingfeng Ding; Jiansong Zhang; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2026)

Sustainable bio-aerogels for food packaging applications: Fabrication strategies, preservation mechanisms, and innovation trends - Xuefeng Liu; Yuqin Feng; Yating Song; Jiajun Guo; Kuiran Liu; Yinghua Tang; Wenhua Mu; Jianfang Li; Yuqing Duan; Guishan Liu (Food Research International, 2026)

The transformation of China's iron and steel industry under carbon constraints: A balance between economy, emission reduction and technical feasibility - Hua Tong; Jun Liu; Yu Wang; Haowen An; Ge Song; Yating Hou; Xiaolong Tang; Honghong Yi (Journal of Environmental Sciences, 2026)

Convection-permitting simulations of hourly precipitation in the Yangtze River Delta region: evaluation and future projections - Yating Xiong; Guangtao Dong; Zhiyu Jiang; Wei Mei; Jianping Tang (Climate Dynamics, 2026)

Dietary quercetin enhances T cell immunity and disease resistance in tilapia via modulating antioxidant and inflammatory responses - Haokai Chen; Jingfeng Ding; Yuqing Yang; Shiqi Tang; Qiqi Jiang; Yuying Zheng; Yating Zhu; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

Review of long-term exposure to road traffic-related air pollution and mortality: Mechanism, exposure, and meta-analysis - Yating Hou; Jun Liu; Xiaolong Tang; Honghong Yi; Tiantian Li; Tong Zhu (Environmental Impact Assessment Review, 2026)

Integrating filtration, pollutant adsorption, and thermal management for enhanced respiratory health: A synergistic framework for next-generation protective masks - Yating Tang; Yun Su; Yiwei Wu; Zhuoling Yu; Mengxian Xu; Miao Tian; Jun Li (Building and Environment, 2026)

Elucidating the degradation behavior and mechanisms of pyraquinil in soil: A comprehensive study on dissipation kinetics, transformation products and toxicity assessment - Xunyuan Jiang; Jiale Wang; Yating Zhang; Congling Huang; Yan Chen; Xuemei Tang; Peiwen Qin; Kai Wan; Hanhong Xu (Pesticide Biochemistry and Physiology, 2026)

The synergistic effect of ambient PM2.5 and psychosocial stress on cardiac health: evidence from a multi-center panel study - Yang Lan; Xianggui Li; Jian Lei; Weidong Zhang; Yunxing Jiang; Kai Wang; Lei Lei; Cuiyao Xie; Yu You; Jiaqi Zhu; Tong Wu; Jie Yan; et al. (Environmental Research, 2026)

Optimization of extraction methods, component identification of bound polyphenols from sea-buckthorn pomace, and its ameliorative effects on oxidative stress in sleep-deprived mice - Jing Peng; Xin Li; Mingyou Yuan; Yating Tang; Tianyi Qiao; Jiaying Li; Haoyang Yu; Meng Zhang; Xiulian Li; Ying Lan (Food Chemistry, 2026)

Cloning and functional study of NADPH-cytochrome P450 reductases and ent-kaurene oxidase from Rhododendron Molle G. Don - Xinmeng Wang; Zheng Liu; Rongfeng Wang; Hao Tang; Ping Su; Xianan Zhang; Xiaoyi Wu; Shurui Zhao; Jiadian Wang; Yating Hu; Luqi Huang (Physiology and Molecular Biology of Plants, 2026)

Achieving a carbon-negative region through carbon sinks and reduction initiatives: A case study of a coastal bay - Yating Zhao; Chang Tang; Jun Zhang; Hongtao Shen; Yahong Dong (Journal of Environmental Management, 2025)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

Integrated process for controlled production of glucuronic acid from microcrystalline cellulose: The evaluation of efficiency and economy - Xia Hua; Yating Hu; Xueyu Tang; Yong Xu (Chemical Engineering Journal, 2025)

A review of low-cost production of polyhydroxyalkanoates: Strategies, challenges, and perspectives - Jian Yao; Xin-Yu Xiao; Meng Wang; Quan Zhang; Yating Chen; Min Gou; Zi-Yuan Xia; Yue-Qin Tang (Bioresource Technology, 2025)

Protocol for Retinal Imaging and Extraction of Imaging-Derived Phenotypes from the Chinese Human Phenome Project - Lizhen Lan; Binxin Xu; Zhiqiang Yan; Yating Tang; Shengli Shen; Xuan Lan; Yidan Gao; Jianhua Jin; Yan Zheng; Chengyan Wang; Jingchun Luo; Mei Tian (Phenomics, 2025)

A voting model weighting algorithm-driven multi-algorithm framework enhances intelligent point-of-care testing for edible oil safety - Zhiqiang Li; Yating Hu; Wen Zhang; Qi Zhang; Peiwu Li; Xiaoqian Tang (Chemical Engineering Journal, 2025)

On-site tracking of trace Aflatoxin B1 in food waste composting via a portable colorimetric sensing platform with nanozymes - Yating Lu; Fuqing He; Xu Zhu; Jing Tang; Yue Lu; Jiajia Wang; Jiangfang Yu; Li Chen; Xingyang Cheng; Tianhao Liu; Lin Tang (Journal of Hazardous Materials, 2025)

An integrated scenario-based approach for carbon reduction pathway decision making - Yating Zhao; Chang Tang; Alun Gu; Yuanfeng Wang; Yahong Dong (Sustainable Cities and Society, 2025)

Sustainable microbial fermentation of plant Proteins: Potential, biological resources, fermentation mechanisms, applications and challenges in food industry - Maosi Fan; Xuelian He; Yating Cao; Kalekristos Yohannes Woldemariam; Min Cai; Zhengkai Wang; Yushan Jiao; Wensheng Tang; Xiaoming Wei; Yingli Liu; Jing Wang (Food Bioscience, 2025)

Recent developments in the fabrication of food microparticles and nanoparticles using microfluidic systems - Xiao Xu; Qi Tang; Yating Gao; Shaoqin Chen; Yingying Yu; Hongliang Qian; David Julian McClements; Chongjiang Cao; Biao Yuan (Critical Reviews in Food Science and Nutrition, 2025)

Effect of cadmium and fumonisin B1 co-exposure on mitochondrial dysfunction and ferroptosis pathway in Caenorhabditis elegans - Yating Wang; Yongli Ye; Jian Ji; Jia-Sheng Wang; Lili Tang; Lanlan Zhang; Yufeng Li; Jiadi Sun; Lina Sheng; Xiulan Sun (Journal of Hazardous Materials, 2025)

Characteristics and Prediction of Reservoir Water Quality under the Rainfall-Runoff Impact by Long Short-Term Memory Based Encoder-Decoder Model - Xiaodan Sheng; Yulan Tang; Shupeng Yue; Xu Yang; Yating He (Water Resources Management, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Characteristics of Phages and Their Interactions With Hosts in Anaerobic Reactors - Yan Zeng; Xiaozhong Zhong; Yating Chen; Min Gou; Ke Yu; Yue‐Qin Tang (Environmental Microbiology, 2025)
Anaerobic digestion (AD) of organic wastes relies on the interaction and cooperation of various microorganisms. Phages are crucial components of the microbial community in AD systems, but their diversity and interactions with the prokaryotic populations are still inadequately comprehended. In this study, 2121 viral operational taxonomic units (vOTUs) were recovered from 12 anaerobic fatty acid–fed reactors. Notably, 63.1% of these vOTUs could not be assigned to any known family, revealing a substantial presence of uncharted phages specifically associated with AD environments. Over half of the vOTUs associated with hosts had the capability to infect multiple hosts, ranging from 2 to 49, with a prevalent tendency to infect 2–5 hosts. In silico predictions of phage‐host linkages uncovered that only a small fraction of vOTUs were shared across different functional groups, including fermentative bacteria, syntrophic fatty acid–oxidising bacteria (SFOB) and methanogens. Phages linked to hosts in all three groups primarily consisted of generalists and temperate species, especially those linked to SFOB. Additionally, metabolic reconstruction identified auxiliary metabolic genes participating in fatty acid degradation, methanogenesis and energy conservation. The present study provides insights into phage characteristics and their in situ interactions with prokaryotic hosts, highlighting their ecological role in AD systems.

Effects of pre-chlorination on ultrafiltration process in directly treating seasonal high-turbidity surface water: Membrane fouling control and shock load resisting - Haochun Wang; Yaru Zhang; Chenghai Lin; Ao Wang; Yanrui Wang; Yating Hu; Shu Jiang; Jinlong Wang; Heng Liang; Xiaobin Tang (Journal of Water Process Engineering, 2024)

Contrasting orbital rhythms preserved in loess grain-size records across the Chinese Loess Plateau - Deai Zhao; Guoqiao Xiao; Chunju Huang; Haibin Wu; Qingzhen Hao; David B. Kemp; Shaohua Tian; Zhipeng Wu; Hao Lu; Gaowen Dai; Shuzhen Peng; Changyan Tang; et al. (Global and Planetary Change, 2024)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Optimized mass transfer of PHI-type zeolite for nitrogen/methane sieve separation - Xuan Tang; Xiaowei Bai; Yating Wang; Xu Yang; Xiaomin Li; Jinping Li; Jiangfeng Yang (Chemical Engineering Journal, 2024)

Maximum diving duration and its influencing factors of diving lizards - Niujin Shi; Yating Liu; Sanqi Tang; Shuyi Luo; Jiasong He; Zhengjun Wu (Behavioral Ecology and Sociobiology, 2024)

Amine response smartphone-based portable and intelligent polyvinyl alcohol films for real-time detection of shrimp freshness - Man Luo; Ji Liu; Yating Zhang; Tao Wang; Xiaomei Ren; Lijuan Gui; Junyuan Zhao; Xuwei Zhang; Yunqing Tang; Ziting Zeng; Fengzhen Hou; Qifeng Zhong; et al. (Food Chemistry, 2024)

Improvement of the ozone forecast over Beijing through combining the chemical transport model with multiple machine learning methods - Jiali Xie; Xiao Tang; Fei Zheng; Xidong Wang; Ning Ding; Yating Song; Hongyan Luo; Huangjian Wu; Lei Kong; Jiang Zhu; Zifa Wang (Atmospheric Pollution Research, 2024)

Convection-permitting regional climate simulations over coastal regions in China - Zhiyu Jiang; Dongqing Liu; Guangtao Dong; Jianping Tang; Shuguang Wang; Yating Xiong (Climate Dynamics, 2024)

Multi-omics association study of hexadecane degradation in haloarchaeal strain Halogranum rubrum RO2-11 - HeLang Huang; CaiYun Xie; ZiYuan Xia; ZhaoYong Sun; YaTing Chen; Min Gou; YueQin Tang; HengLin Cui; XiaoLei Wu (Environmental Research, 2024)

Fusion of Multi-Layer Attention Mechanisms and CNN-LSTM for Fault Prediction in Marine Diesel Engines - Jiawen Sun; Hongxiang Ren; Yating Duan; Xiao Yang; Delong Wang; Haina Tang (Journal of Marine Science and Engineering, 2024)
Timely and effective maintenance is imperative to minimize operational disruptions and ensure the reliability of marine vessels. However, given the low early warning rates and poor adaptability under complex conditions of previous data-driven fault prediction methods, this paper presents a hybrid deep learning model based on multi-layer attention mechanisms for predicting faults in a marine diesel engine. Specifically, this hybrid model first introduces a Convolutional Neural Network (CNN) and self-attention to extract local features from multi-feature input sequences. Then, we utilize Long Short-Term Memory (LSTM) and multi-head attention to capture global correlations across time steps. Finally, the hybrid deep learning model is integrated with the Exponential Weighted Moving Average (EWMA) to monitor the operational status and predict potential faults in the marine diesel engine. We conducted extensive evaluations using real datasets under three operating conditions. The experimental results indicate that the proposed method outperforms the current state-of-the-art methods. Moreover, ablation studies and visualizations highlight the importance of fusing multi-layer attention, and the results under various operating conditions and application scenarios demonstrate that this method possesses predictive accuracy and broad applicability. Hence, this approach can provide decision support for condition monitoring and predictive maintenance of marine mechanical systems.

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Autophagy inhibition mediated by trillin promotes apoptosis in hepatocellular carcinoma cells via activation of mTOR/STAT3 signaling - Guangjie Zhan; Tiantian Wei; Huichen Xie; Xiaoming Xie; Jun Hu; Hao Tang; Yating Cheng; Huaifeng Liu; Shujing Li; Guohua Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Improved high-temperature sintering resistance and light alkanes oxidation activity by La modification on Co3O4 nanocatalyst - Yijia Cao; Jinyan Xiao; Yating Lv; Shengwei Tang; Liaoyong Wen; Wenxiang Tang (Fuel, 2024)

Effects of acute and chronic chromium stress on the expression of heat shock protein genes and activities of antioxidant enzymes in larvae of Orthetrum albistylum - Tingting Ma; Yanjuan Ding; Fengjiao Xu; Chen Zhang; Min Zhou; Ya Tang; Yanrong Chen; Yating Wen; Rufei Chen; Bin Tang; Shigui Wang (Environmental Pollution, 2024)

Induced Resistance Mechanism of Bacillus velezensis S3-1 Against Pepper Wilt - Yongjie Fan; Xingjie He; Jiawei Dai; Ning Yang; Qiuyan Jiang; Zhaofeng Xu; Xiaorong Tang; Yating Yu; Ming Xiao (Current Microbiology, 2023)

Field experiment and numerical simulation for airflow evaluation in a data center with row-based cooling - Yating Wang; Xuelian Bai; Yusen Fu; Yu Tang; Chaoqiang Jin; Zuoyang Li (Energy and Buildings, 2023)

Soil acidification induced variation of nitrifiers and denitrifiers modulates N2O emissions in paddy fields - Chaobiao Meng; Yating Xing; Yu Ding; Qichun Zhang; Hongjie Di; Caixian Tang; Jianming Xu; Yong Li (Science of The Total Environment, 2023)

A Genome-Wide Association Study for Susceptibility to Axial Length in Highly Myopic Eyes - Qiang Lu; Yu Du; Ye Zhang; Yuxi Chen; Hao Li; Wenwen He; Yating Tang; Zhennan Zhao; Yinglei Zhang; Jihong Wu; Xiangjia Zhu; Yi Lu (Phenomics, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Investigating the Changes in Air Pollutant Emissions over the Beijing-Tianjin-Hebei Region in February from 2014 to 2019 through an Inverse Emission Method - Xuechun Luo; Xiao Tang; Haoyue Wang; Lei Kong; Huangjian Wu; Weiguo Wang; Yating Song; Hongyan Luo; Yao Wang; Jiang Zhu; Zifa Wang (Advances in Atmospheric Sciences, 2023)

Efficient removal of uranium(VI) from aqueous solution by a novel phosphate-modified biochar supporting zero-valent iron composite - Ziwei Tang; Zhongran Dai; Mi Gong; Hong Chen; Xiayu Zhou; Yating Wang; Cong Jiang; Wanying Yu; Le Li (Environmental Science and Pollution Research, 2023)

Cobalt induces neurodegenerative damages through impairing autophagic flux by activating hypoxia-inducible factor-1α triggered ROS overproduction - Jianping Tang; Yanjun Li; Xu Liu; Guangxia Yu; Fuli Zheng; Zhenkun Guo; Yating Zhang; Wenya Shao; Siying Wu; Huangyuan Li (Science of The Total Environment, 2023)

The race to develop oral SERDs and other novel estrogen receptor inhibitors: recent clinical trial results and impact on treatment options - Yating Wang; Shou-Ching Tang (Cancer and Metastasis Reviews, 2022)
Hormonal therapy plays a vital part in the treatment of estrogen receptor–positive (ER +) breast cancer. ER can be activated in a ligand-dependent and independent manner. Currently available ER-targeting agents include selective estrogen receptor modulators (SERMs), selective estrogen receptor degraders (SERDs), and aromatase inhibitors (AIs). Estrogen receptor mutation (ESR1 mutation) is one of the common mechanisms by which breast cancer becomes resistant to additional therapies from SERMs or AIs. These tumors remain sensitive to SERDs such as fulvestrant. Fulvestrant is limited in clinical utilization by its intramuscular formulation and once-monthly injection in large volumes. Oral SERDs are being rapidly developed to replace fulvestrant with the potential of higher efficacy and lower toxicities. Elacestrant is the first oral SERD that went through a randomized phase III trial showing increased efficacy, especially in tumors bearing ESR1 mutation, and good tolerability. Two other oral SERDs recently failed to achieve the primary endpoints of longer progression-free survival (PFS). They targeted tumors previously treated with several lines of prior therapies untested for ESR1 mutation. Initial clinical trial data demonstrated that tumors without the ESR1 mutation are less likely to benefit from the SERDs and may still respond to SERMs or AIs, including tumors previously exposed to hormonal therapy. Testing for ESR1 mutation in ongoing clinical trials and in hormonal therapy for breast cancer is highly recommended. Novel protein degradation technologies such as proteolysis-targeting chimera (PROTACS), molecular glue degrader (MGD), and lysosome-targeting chimeras (LYTACS) may result in more efficient ER degradation, while ribonuclease-targeting chimeras (RIBOTAC) and small interfering RNA (siRNA) may inhibit the production of ER protein.

The Impact of the Numbers of Monitoring Stations on the National and Regional Air Quality Assessment in China During 2013–18 - Hongyan Luo; Xiao Tang; Huangjian Wu; Lei Kong; Qian Wu; Kai Cao; Yating Song; Xuechun Luo; Yao Wang; Jiang Zhu; Zifa Wang (Advances in Atmospheric Sciences, 2022)

Three Novel Mutations of Microphthalmos Identified in Two Chinese Families - Yating Tang; Jie Xu; Yi Lu; Tianyu Zheng (Phenomics, 2022)

Preoperative Characteristics of Ocular Biometry in Children with Unilateral Congenital Cataracts - Jiahui Chen; Yating Tang; Yongxiang Jiang; Yi Lu (Phenomics, 2022)